The Routledge international handbook of children's rights and disability - Beckett, Angharad E.; Callus, Anne-Marie (UK : Routledge, 2023)
"This handbook provides authoritative and cutting-edge analyses of various aspects of the rights and lives of disabled children around the world. Taking the UN Convention on the Rights of Persons with Disabilities (CRPD) and the UN Convention of the Rights of the Child (CRC) as conceptual frameworks, this work appraises the current state of affairs concerning the rights of disabled children across different stages of childhood, different life domains and different sociocultural contexts. It will be of interest to researchers and students working in disability studies, education, allied health, law, philosophy, play studies, social policy, and the sociology of childhood. It will also be a valuable resource for professionals/practitioners, allowing them to consider future directions for ensuring that disabled children's rights are realized and their well-being and dignity is assured"--
Includes bibliographical references and index.
English.
Keywords: Children with disabilities -- Legal status, laws, etc; Children with disabilities -- Social conditions; Children's rights